DIFFERENTIAL – PSYCHOLOGICAL ASPECTS OF THE METHOD OF FIXATED SET: EMPIRICAL VERIFICATION - Robakidze, Maia (Georgian Psychological Journal, 2023)
Several decades passed after development of the experimental method in the psychology of set. In spite of this, it still arises interest in the modern studies of medical psychology and psychophysiology. Many researchers from different countries use the above method, known as “Uznadze effect”. Differently from most Georgian studies dedicated to the psychology of set, foreign colleagues use modern refined technologies and statistical methods in their experiments. For this reason, we decided to conduct set experiments with the use of software program and modern methods of statistical analysis to verify the findings related to individual types of fixated set and personality traits. 171 participated in the experiment on the fixation of set. The experiment followed Uznadze’s classical method, but with the use of special software developed for visual modality. In addition, research participants’ responses were automatically recorded. Research participants also completed the validated Georgian versions of Big Five personality test (NEO-FFI) and Spielberger inventory (STAI) measuring personal anxiety. Dispersion analysis showed that static type is characterized with a higher level of neuroticism and personal anxiety than the dynamic type. Also, the plastic type scores higher on extraversion than the individuals with coarse type of set. Logistic regression analysis showed that neuroticism is a predictor of the dynamics of the extinction process (predictor of staticity – dynamism).